A ranking method based on handicaps - Gabrielle Demange (Theoretical Economics, 2014)
Ranking methods are fundamental tools in many areas. Popular methods aggregate the statements of `experts' in different ways. As such, there are various reasonable ranking methods, each one of them more or less adapted to the environment under consideration.This paper introduces a new method, called the handicap-based method, and characterizes it through appealing properties. This method assigns not only scores to the items but also weights to the experts. Scores and weights form an equilibrium for a relationship based on the notion of handicaps. The method is, in a sense made precise in the paper, the counterpart to the counting method in environments that require intensity-invariance. Intensity-invariance is a desirable property when the intensity of the experts' statements has to be controlled. Otherwise, both the counting and handicap-based methods satisfy a property called homogeneity, which is a desirable property when cardinal statements matter, as is the case in many applications.
Keywords: D71; D89; 330; Ranking; scores; invariant method; peers' method; handicap; scaling matrix